Fimasartan attenuates renal ischemia-reperfusion injury by modulating inflammation-related apoptosis - Cho, Jang-Hee (Korean J Physiol Pharmacol, 2018)
Fimasartan, a new angiotensin II receptor antagonist, reduces myocyte damage and stabilizes atherosclerotic plaque through its anti-inflammatory effect in animal studies. We investigated the protective effects of pretreatment with fimasartan on ischemia-reperfusion injury (IRI) in a mouse model of ischemic renal damage. C57BL/6 mice were pretreated with or without 5 (IR-F5) or 10 (IR-F10) mg/kg/day fimasartan for 3 days. Renal ischemia was induced by clamping bilateral renal vascular pedicles for 30 min. Histology, pro-inflammatory cytokines, and apoptosis assays were evaluated 24 h after IRI. Compared to the untreated group, blood urea nitrogen and serum creatinine levels were significantly lower in the IR-F10 group. IR-F10 kidneys showed less tubular necrosis and interstitial fibrosis than untreated kidneys. The expression of F4/80, a macrophage infiltration marker, and tumor necrosis factor (TNF)-α, decreased in the IR-F10 group. High-dose fimasartan treatment attenuated the upregulation of TNF-α, interleukin (IL)-1β, and IL-6 in ischemic kidneys. Fewer TUNEL positive cells were observed in IR-F10 compared to control mice. Fimasartan caused a significant decrease in caspase-3 activity and the level of Bax, and increased the Bcl-2 level. Fimasartan preserved renal function and tubular architecture from IRI in a mouse ischemic renal injury model. Fimasartan also attenuated upregulation of inflammatory cytokines and decreased apoptosis of renal tubular cells. Our results suggest that fimasartan inhibited the process of tubular injury by preventing apoptosis induced by the inflammatory pathway.